If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 8x = -18 Solving 6 + 8x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 8x = -18 + -6 Combine like terms: 6 + -6 = 0 0 + 8x = -18 + -6 8x = -18 + -6 Combine like terms: -18 + -6 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 3x+10=10-7x | | 0.75x+5=6 | | 6r-2r+2=7r-r | | -178-10x=44-31x | | 3-1/3= | | (5x-6)1/2=7 | | -3z-2(3+5z)= | | -8=y-6y-6 | | 1+7x=-13 | | s-9=r | | 1/2(4+6)=0 | | x^1/2+x=0 | | 78-7x=20x+15 | | -9=r | | -(7x-4)+4x-5=-1 | | 6-10x=39-17x | | -144=-12x | | -(6x-4)+4x-6=-2 | | 11.4(x+3)+2=4.5(x+1) | | 5n-2n=-9 | | -12*12= | | 2.625=fraction | | 5=5+2m+3m | | 12*-12= | | 7(-16)(0)(-3)= | | Y=-25+4(x+5) | | x+x+4+3(x)+7=71 | | 1x+8=8x+22 | | 9x=3y-6 | | 13x+5=1x+11 | | 0.5a+2=5 | | 9x+15=3x+17 |